Allele specific silencing of proteins at the neuromuscular junction - Biba, A (2009)
RNA interference (RNAi) is a post transcriptional gene silencing mechanism that allows potent and specific silencing of cognate mRNA transcripts. Selective silencing can be used to dissect complex polygenic diseases, elucidate the function of known genes and provide a tool for genetic therapy. Its use in the case of dominant inherited disorders including disorders of the central nervous system, depends on its ability to confer single nucleotide discrimination between normal and mutant gene alleles. In this thesis the ability of RNAi effector molecules to provide single nucleotide specificity was examined by targeting two dominant inherited mutations of the acetylcholine receptor that cause slow-channel syndrome. Allele-specific silencing was achieved for one mutation. The other mutation was also silenced but not in an allele specific way despite employing known techniques for increasing single-nucleotide specificity. The model used in this thesis is the congenital myasthenia slow-channel syndrome. This is a dominant inherited disorder of the neuromuscular junction which is both well-characterised and more readily accessible compared to the central nervous system, thus provides a prototype for development of allele-specific RNAi therapeutics. Here we describe a new transgenic animal model of the slow-channel syndrome and show good representation of the human disorder. The need for defining the characteristics that determine the effectiveness and the specificity of RNAi effectors at single-nucleotide level, along with the future uses of the newly described animal model are discussed.